KAJIAN TENTANG BELAJAR KEPEMIMPINAN DARI PEMIMPIN TERBAIK - Yudistira Adi Nugroho (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
According to data submitted by the Corruption Eradication Commision indicates there are still many leaders both at the central and regional levels that are involved in legal issues. This study aims to know and analyze of leadership that exist in Muhammad Al-Fatih in accordance with the development of modern knowledge. Through this study can give an idea of ​​how to become a leader that is expected by the community. For research purposes, the method used with descriptive approach through library research (library research). Data collection in this research by collecting various materials from books, journals, research results, newspapers, bulletins, as well as other necessary data and information. Analytical techniques use analytic patterns by identifying and comparing Mohammad al-Fatih's best practice leadership with emerging modern knowledge. The analytic pattern is an activity that contains a number of activities such as parsing, differentiating, sorting something to be classified and regrouped according to certain criteria then searched for and interpreted meaning. The results show that Muhammad Al Fatih is an adaptive and flexible leader. In addition, the leadership of Muhammad Al Fatih is a blend of capable abilities as a human being coupled with a touch of high spiritual values. Muhammad Al Fatih is a superior leader character according to the current leadership concept. Keywords: Muhammad al Fatih, Leader, Leadership